New specimen of Clypeotherium magnum Scillato-Yané (Cingulata, Xenarthra) from the Oligocene of Patagonia, Argentina - Gonzalez Ruiz, Laureano Raul (2022)
Clypeotherium magnum Scillato-Yané, the only species of that monospecific genus, is only known through its type material, represented by osteoderms from the carapace (MLP 61-IV-11-76), collected in 1960 (and described in 1977) by MLP staff at El Pajarito fossil locality in Chubut province (Sarmiento Formation, late Oligocene, Deseadan SALMA), and also by osteoderms (MCNAM) from Quebrada Fiera locality in Mendoza province (Agua de la Piedra Formation, late Oligocene, Deseadan SALMA) described and assigned to Clypeotherium sp. in 2021. A new specimen of C. magnum is identified (AMNH 96285), represented by 21 probably associate osteoderms of the carapace, collected in 1933 by AMNH staff (Scarritt Expedition led by G.G. Simpson) at Cañadón de las Víboras fossil locality in Chubut province (Sarmiento Formation, late Oligocene, Deseadan SALMA). The diagnostic characters of C. magnum, also present in the new specimen, includes: 1) osteoderms with a large flat or slightly convex central figure; 2) few peripheric figures restricted to the anterior and lateral regions of the osteoderms; 3) large foramina on the sulci that delimit the figures of the osteoderms. Two of the osteoderms are of special significance, because they belong to the laterodorsal region of the carapace, having a quadrangular outline; the exposed surface shows a “rosette” pattern, with a central figure displaced posteriorly, surrounded by 3-4 anterior large peripherical figures, and by 3 smaller posterior figures; these posterior figures, although reduced in size, are present. The remaining osteoderms show a typical “Glyptatelinae” pattern, having mostly 3 large anterior peripheral figures and the absence (or only 1) of posterior peripheral figures. The absence of posterior peripherical figures is considered a plesiomorphic character, meanwhile, the presence in Clypeotherium magnum (at least in some regions of the carapace) should be analyzed in future phylogenetical studies. This new specimen increases the geographical distribution of the genus to a third fossil locality (although still restricted to high latitudes) and the detailed description and comparison of this specimen will lead us to a better understanding of this poorly known cingulate.